Dialogues between sociocultural issues and knowledge organization systems - Moreira, Walter [UNESP]; Sabbag, Deise (Ibersid, 2022)
The necessary ontological basis for knowledge organization systems (KOS) is structured on an epistemological basis and as is increasingly required in the context of critical knowledge organization studies, on a cultural basis. Thus, KOS must be discussed in terms of their social impacts, either directly or indirectly, visible, or not. The following questions are raised as general research problems: how to recognize and incorporate cultural diversity in KOS? How do recognize its applied dimension in the construction of documentary representations? KOS that are not inclusive fail in their fundamental purpose, which is the socialization of knowledge. The neglect of the cultural variables involved in the production and organization of knowledge makes the system oppressive or irrelevant, in both cases expendable. Thus, the objective is to understand the new requirements formulated for knowledge organization systems in accordance with the interests of the cultural perspective of knowledge organization. To do this, the construction of a critical-reflexive text based on the elements indicated by Hjørland and Pedersen (2005) and summarized in Hjørland (2008) as foundations for a classification theory is adopted as a methodological parameter. Thus, the ten principles listed by these authors are systematized into five dimensions of analysis related to the conception of the classificatory structure as a key component of KOS, they are: objectivity/subjectivity; ontological basis; sociocultural base; the domain as a guiding element; social effects of classification. It is concluded that the incorporation of cultural diversity into KOS requires attention to, at least, three elements that, although easily identifiable, prove to be extremely complex in their pragmatic aspect: a) the mapping and recognition of the different sociocultural perspectives through which a given concept can be observed; b) the incorporation of this diversity into the SOCs by making the classification structure that supports it more flexible; c) the explanation of the points of view adopted in the construction of the SOC.
Diálogos entre las cuestiones socioculturales y los sistemas de organización del conocimiento
Diálogos entre as questões socioculturais e os sistemas de organização do conhecimento
Keywords: Cultural studies; Knowledge organization; Knowledge organization systems; Social issues